How Are Fenebahçe’s And Beşiktaş’s Stock Returns Reacted To The Match-Fixing Announcement? - Hülya Ünlü; Merve Karacaer Ulusoy (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Football is one of the most important sport activities in the worldwide, where stock prices are very sensitive to game results. On 3rd of July 2011 Beşiktaş and Fenerbahçe, the two major Turkish soccer teams, were accused of match-fixing which suddenly dampen their share prices. This study assesses to compare the stock market performances of both Beşiktaş and Fenerbahçe when they earn the right to enter group stages in UEFA European League before the match-fixing and after the match-fixing announcement by using event study method. The results indicate that the announcement of entering group stages in UEFA European League before the match-fixing process has a positive impact on both teams’ stock movements. On the other hand, after the announcement of match-fixing, negative effect is achieved for both of the teams, even they earned the right to enter group stages. Interestingly the evidences show that Fenerbahçe’s stocks are affected heavily during the match fixing process while the same negative effect is not strong for Beşiktaş. The findings of this study will contribute to the literature as it is the only study that compares the effect of match-fixing process on the stock market returns of both Beşiktaş and Fenerbahçe when these teams are successful in international areas by considering UEFA European League as the case.